2002
DOI: 10.1016/s0161-5890(02)00202-x
|View full text |Cite
|
Sign up to set email alerts
|

High affinity binding of long-chain polysialic acid to antibody, and modulation by divalent cations and polyamines

Abstract: Long-chain polysialic acid (PSA) is expressed on the vertebrate neural cell adhesion molecule (NCAM) during neuronal plasticity. Its structural similarity to the capsular PSAs of some pathogenic bacteria has hampered the development of polysaccharide vaccines against meningitis. The antibodies formed during immunization require a long epitope for binding, and cross-react with host tissue PSA. The nature of the epitope and possible external effectors involved are still unclear. We have evaluated the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Incubation at 4°C was previously demonstrated to increase binding of anticapsular antibody to MenB polysaccharide (1,30). However, we demonstrated that temperature did not affect inhibition with colominic acid (data not presented), in agreement with previous reports of Hayrinen and coworkers (11,12,13). Increased incubation periods and agitation conditions were also investigated but, again, showed no effect on inhibition or SBA titers (data not presented).…”
Section: Discussionsupporting
confidence: 92%
“…Incubation at 4°C was previously demonstrated to increase binding of anticapsular antibody to MenB polysaccharide (1,30). However, we demonstrated that temperature did not affect inhibition with colominic acid (data not presented), in agreement with previous reports of Hayrinen and coworkers (11,12,13). Increased incubation periods and agitation conditions were also investigated but, again, showed no effect on inhibition or SBA titers (data not presented).…”
Section: Discussionsupporting
confidence: 92%
“…Microtiter plates were coated with polySia containing a lipid anchor (20) to allow efficient attachment of polySia to the solid phase (14). After endoNF digestion and removal of the enzyme, remaining substrate was detected with the polySia-specific monoclonal antibody 735, which binds to ␣2,8-linked polySia Ն8 residues (22,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…3). Staining was performed either with mAb 735 (top panel) specific for ␣2,8-linked polySia with DP Ն 8 (39,44) or mAb H28 (middle and bottom panels) directed against a protein epitope common to all murine NCAM isoforms (38). Because each polySia chain provides multiple binding sites for an antipolySia antibody, much stronger signals were obtained with mAb 735.…”
Section: and St8siaivmentioning
confidence: 99%